KELENGKAPAN PENCATATAN BERAT BADAN ANAK PADA BUKU KIA ANTARA PESERTA PKH DAN BUKAN PESERTA PKH - Dwijayanti, Krisnita; Nurkhalim, Ratna Frenty; Susilowati, Indah (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
Program Keluarga Harapan (PKH) is a program that providing assistance cash to the very poor households the purpose the improvement of health status child under 6 years. The study aimed to see if there is a diference in completenes charging weight a child at maternal child health book between participant PKH and not participant PKH. This research is a quantitative research using  retrospective design. Was used 171 in the study of secondary data on maternal child health book in tanjunganom sub-district of nganjuk regency. Chi-square test results showed that the completenes charging weight a child at maternal child health book between participant PKH and not participant PKH significance are >0,05 (0,112). This mean no signofocant differences betwen participant PKH and are not participant PKH completeness charging at maternal child health book. In conclusion, there is no difeerence completeness charging weight children between participants and non-PKH in tanjunganom sub-district of nganjuk regency.